2021
DOI: 10.1002/cti2.1310
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the growth hormone‐releasing hormone antagonist MIA602 and its underlying mechanisms of action in sarcoidosis‐like granuloma

Abstract: Objectives. Growth hormone-releasing hormone (GHRH) is a potent stimulator of growth hormone (GH) secretion from the pituitary gland. Although GHRH is essential for the growth of immune cells, the regulatory effects of its antagonist in granulomatous disease remain unknown. Methods. Here, we report expression of GHRH receptor (R) in human tissue with sarcoidosis granuloma and demonstrate the anti-inflammatory effects of MIA602 (a GHRH antagonist) in two in vitro human granuloma models and an in vivo granuloma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Among these analogs, MIA-602 and MIA-690 showed potent suppressive effects on the growth of many cancers, including lung, gastric and colorectal cancers, where they exerted anti-inflammatory, antioxidative and proapoptotic functions [ 23 , 24 , 25 ]. Importantly, MIA-602, also reduced inflammation and fibrosis in a mouse model of lung injury, by inhibiting inflammatory pathways, such as signal transducer and activator of transcription 3 (STAT3) and nuclear factor kappa-B (NF-kB) [ 26 , 27 ], and decreased inflammation in sarcoidosis-like granuloma [ 28 ]. Furthermore, we recently demonstrated that MIA-602 and MIA-690, as single agents, inhibit the growth of human PM cell lines and primary cells in vitro, and exert strong antitumor effects in vivo in PM mice, by blunting proliferative and oncogenic pathways, as well as expression of tumor insulin-like growth factor 1 (IGF-1) and vascular endothelial growth factor (VEGF) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these analogs, MIA-602 and MIA-690 showed potent suppressive effects on the growth of many cancers, including lung, gastric and colorectal cancers, where they exerted anti-inflammatory, antioxidative and proapoptotic functions [ 23 , 24 , 25 ]. Importantly, MIA-602, also reduced inflammation and fibrosis in a mouse model of lung injury, by inhibiting inflammatory pathways, such as signal transducer and activator of transcription 3 (STAT3) and nuclear factor kappa-B (NF-kB) [ 26 , 27 ], and decreased inflammation in sarcoidosis-like granuloma [ 28 ]. Furthermore, we recently demonstrated that MIA-602 and MIA-690, as single agents, inhibit the growth of human PM cell lines and primary cells in vitro, and exert strong antitumor effects in vivo in PM mice, by blunting proliferative and oncogenic pathways, as well as expression of tumor insulin-like growth factor 1 (IGF-1) and vascular endothelial growth factor (VEGF) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…We collected their left lungs for pathology after removing blood. We used H&E staining to determine inflammatory pathology [ 11 ]. For IHC, we used primary antibodies (CD68, PD-1, PD-L1, CD30) and secondary antibodies, all purchased from Cell Signaling Technology, Beverly, MA, USA [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…We used H&E staining to determine inflammatory pathology [ 11 ]. For IHC, we used primary antibodies (CD68, PD-1, PD-L1, CD30) and secondary antibodies, all purchased from Cell Signaling Technology, Beverly, MA, USA [ 11 ]. ABC Elite kit (Cat# PK-6200 Vector Laboratories, Inc. Burlingame, CA, USA) was used to detect immunoreaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At mRNA level MIA-602 downregulates pathways involved in adaptive immune responses including T cell activation and differentiation, T cell signaling and cytokine production ( 54 ). In a sarcoidosis granuloma model, GHRHR inhibition results in reduced IL-12 and IL-17A production ( 54 , 55 ). Thus, MIA-602 demonstrates the contribution of GHRHR to adaptive immunity and T cell function, and that GHRHR is a potential candidate for managing these responses when they are excessive, such as in granulomatous diseases.…”
Section: Central Endocrine (Hypothalamic and Pituitary) Hormonesmentioning
confidence: 99%